Cross‐resistance risk of the novel complex II inhibitors cyenopyrafen and cyflumetofen in resistant strains of the two‐spotted spider mite Tetranychus urticae. Issue 3 (2nd October 2013) - Khalighi, Mousaalreza; Tirry, Luc; Van Leeuwen, Thomas
Abstract BACKGROUND Cyflumetofen and cyenopyrafen are novel acaricides acting as complex II inhibitors. This new mode of action is extremely useful for devising efficient resistance management strategies for mite control. The authors determined the cross‐resistance risk of both compounds, using a collection of well‐characterised resistant strains of Tetranychus urticae, and also selected for cyflumetofen resistance in the laboratory. RESULTS Cross‐resistance to cyflumetofen and cyenopyrafen was detected in field strains, with LC50 values exceeding the registered field dose. Synergism experiments suggested that P450 monooxygenases are involved in resistance, and that the activation mechanism of the two compounds most likely differs. Laboratory selection with cyflumetofen resulted in a highly resistant T. urticae strain that displayed negative cross‐resistance to cyenopyrafen. CONCLUSIONS The cross‐resistance risk of cyflumetofen and cyenopyrafen documented in this study needs to be integrated in resistance management strategies, especially in regions or crops with a history of frequent acaricide applications, in order to safeguard the efficacy of these compounds with a valuable new mode of action. © 2013 Society of Chemical Industry